Can bone-regulating hormones and nutrients help characterize the metabolically healthy obese phenotype. Issue 3 (September 2018) - Sukumar, Deeptha; Becker, Kendra B; Cheung, May; Diamond, Samantha; Duszak, Rittane; Aljahdali, Abeer; Volpe, Stella L; Nasser, Jennifer A
Background: Bone-regulating hormones and nutrients play an important role in influencing metabolic health. Aim: The aim of this study was to determine whether bone-regulating hormones and nutrients, such as parathyroid hormone (PTH), 25-hydroxyvitamin D (25OHD), and magnesium (Mg) could be used to characterize the metabolically healthy obese (MHO) phenotype. Methods: This study included 27 overweight or obese participants (14 men/13 women) classified as MHO ( n = 14) or metabolically unhealthy obese (MUO) ( n = 13) based on the presence or absence of metabolic abnormalities, determined by percentage body fat, percentage trunk fat, and waist circumference. Biochemical (serum concentrations of hormones and cytokines such as PTH, 25OHD, ionized Mg (iMg), cytokines, lipids, glycemic indices), physiological (percentage body fat, percentage trunk fat, blood pressure (BP)), and dietary intake (Mg intake, calcium intake) measurements were obtained. Results: Serum PTH concentrations were significantly lower ( p = 0.005) in the MHO group (39.68 ± 11.06 pg/mL) compared with the MUO group (63.78 ± 25.82 pg/mL). Serum iMg concentrations were higher ( p = 0.052) in the MHO group (0.565 ± 0.41 mmol/L) than in the MUO group (0.528 ± 0.050 mmol/L). Serum concentrations of osteocalcin were also higher (10.37 ± 3.70 ng/mL) in the MHO compared with the MUO (6.51 ± 4.14 ng/mL) group ( p = 0.017). The MHO group had significantly lower serum insulin concentrations ( p = 0.006) and diastolic BP ( p = 0.035). Concentrations of serum 25OHD, total triglycerides, C-reactive protein and systolic BP did not differ between groups. Conclusions: These findings suggest that bone-regulating hormones and nutrients, especially serum PTH, osteocalcin concentrations, and dietary Mg intakes, can help to characterize the MHO phenotype.